Orientalist and Multiculturalist Representations in Chinese-American Literature: Imagological and Hermeneutic Interpretation of The Woman Warrior and The Kitchen God's Wife - Caifeng, Xiao (My University, 2010)
This study aims to examine Orientalist and multiculturalist representations in the production of Chinese-American authors. The research is literary in nature, investigating both academic and social arguments that are depicted in the central works of two chosen authors: namely, Maxine Hong Kingston’s The Woman Warrior and Amy Tan’s The Kitchen God’s Wife. Edward Said’s synthesis of Orientalism and Charles Taylor’s elaboration on multiculturalism will serve as the theoretical background of this study. Imagological literary research is one of the most important disciplines within the field of Comparative Literature, and its function is to examine cultural identity, various national characters and stereotypes. For the purpose of the present thesis, an imagological approach provides a supportive framework which helps to analyze manifestations of Orientalism in the selected novels. Through analyzing the protagonists, Chinese alimentary image, landscape of China town and Chinese superstition, Orientalism emerges to the surface. For the hermeneutics of multiculturalism, the study has indicated that intertextuality of Chinese myth, storytelling of Chinese experience, and mother-child relationship function to construct a bridge for Chinese and American culture to communicate, negotiate, and interact. The study also reveals that Chinese and American cultural difference plays a crucial role in generating confrontation between Chinese mothers and their American-born daughters. In order to search for ethnicity and recognition in White-dominant America, Chinese Americans should pay equal attention to both Chinese and American culture so that both can coexist.
Keywords: Orientalism; multiculturalism; imagology; hermeneutics; Chinese-American literature; fi=Englannin kieli|en=English language|; fi=Master's Degree Programme in Intercultural Studies in Communication and Administration|